MENINGKATKAN HASIL BELAJAR PAI DENGAN MENGGUNAKAN METODE DISKUSI DI SDN 13 PANDAM - Hafni Hafni (Adiba Aisha Amira, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) among fifth-grade students at SD Negeri 13 Pandam through the implementation of the discussion method. The research method used is Classroom Action Research (CAR) based on the spiral model of Kemmis and McTaggart, which includes planning, implementation, observation, and reflection in two cycles. Research data were collected through formative tests, observations, and interviews. The results of the study indicate that the implementation of the discussion method successfully enhanced students' learning outcomes in cognitive, affective, and psychomotor aspects. In Cycle I, the percentage of students achieving mastery learning was 49.1%, with an average score of 71.8. In Cycle II, the mastery percentage increased to 81.8%, with an average score of 80.5. These findings demonstrate that the discussion method is effective in improving PAI learning outcomes, particularly on the topic of living peacefully in diversity, as related to QS. Ali 'Imran: 64 and QS. Al-Baqarah: 256.